TRANSPARENCY ACCORDING TO THE S&P500 INDICES AND ITS IMPLICATIONS FOR THE VALUE OF THE ENTERPRISE UNDER TOBIN’S Q MODEL AN APPLIED STUDY OF A SAMPLE OF IRAQI PRIVATE BANKS FOR THE PERIOD FROM 2016 TO 2021" - Mohammed Abd Ali M.A. Al Fattehallah; Mohammed Hwueish Allawi Alsujair (Galaxy International Interdisciplinary Research Journal, 2022)
The current research aims to compare the models applied to the S&P500 indices locally and regionally, to test and analyze the relationship between the level of transparency of accounting disclosure and the value of commercial banks according to Tobin’s Q model, for a sample of private commercial banks listed on the Iraq Stock Exchange. The transparency of disclosure was evaluated using the S&P500 indices, consisting of 98 requirements in the original scale, with indices of the same scale modified and reduced by the measurers.